Comprehensive outcomes of on‐ and off‐antiviral prophylaxis in hepatitis B patients undergoing cancer chemotherapy: A competing risks analysis. Issue 9 (5th April 2016) - An, Jihyun; Shim, Ju Hyun; Kim, Seon‐Ok; Choi, Jonggi; Kim, Sang‐We; Lee, Danbi; Kim, Kang Mo; Lim, Young‐Suk; Lee, Han Chu; Chung, Young‐Hwa; Lee, Yung Sang; Suh, Dong Jin
Abstract : Although antiviral prophylaxis is essential in hepatitis B patients in the context of cancer chemotherapy, there is little evidence‐based consensus regarding the appropriate prevention strategy depending on the underlying type of cancer and viral status. This retrospective study included a comprehensive cohort of 302 hepatitis B surface antigen‐positive patients with various cancers undergoing chemotherapy and antiviral prophylaxis. The rates of hepatitis B virus (HBV) reactivation during antiviral therapy (>1 log10 IU/mL increase or positive conversion of serum HBV DNA) and relapse when off antivirals ([re]appearance of HBV DNA >2, 000 IU/ml with related alanine aminotransferase elevation) were evaluated, together with the associated risk factors, in a competing risks analysis where cancer death was considered as the competing event. During antiviral prophylaxis, HBV was reactivated in six patients (1.9%), who had leukemia (n = 4) or lymphoma (n = 2) and were treated with lamivudine (n = 4) or entecavir (n = 2). The incidence rate of HBV relapse in 127 off‐prophylaxis patients was 21.3% during a median post‐antiviral period of 11.7 months. Lymphoma, pre‐prophylactic HBV DNA ≥2, 000 IU/ml, and age ≥50 years were independent predictors of off‐treatment HBV relapse (adjusted hazard ratios 5.25, 3.07, and 0.34, respectively; P s < 0.05). Antiviral and anticancer drugs, duration of consolidation on antiviral prophylaxis, and HBeAg positivity were not independent predictors. In conclusion, hepatitis B flare‐ups are not rare in patients receiving cancer chemotherapy during and after anti‐HBV prophylaxis, even when potent antivirals are used. Patients with hematopoietic or lymphoid neoplasms or high viral burdens should receive prolonged and powerful HBV prophylaxis. J. Med. Virol. 88:1576–1586, 2016 . © 2016 Wiley Periodicals, Inc.